Career counseling comphrehensive to develop enterpreneurship vocational students in Jakarta - Naniek K Darmawan; untika Nurihsan; Uman Suherman AS (1st ASEAN School Counselor Conference on Innovation and Creativity in Counseling)
This paper investigates conceptual framework and empirical bases of career counseling to enhance students’ entrepreneurship skills among secondary vocational school students. By comprehensive services through self-help intervention might help guidance and counselling teachers in delivering entrepreneurship attitude beyond of entrepreneurship competences. For developing esnterpreneurship’s students by comprehensive intervention model, preliminary study conducted as a basis for the model. In this study, 200 Vocational school students participated in the survey which involved 5 schools in DKI Jakarta by using Stage Random Sampling. The result will shows the effectiveness based on the findings, recommendations were made for model development.